The Meaning and Cultural Value of the Empty Horse Phenomenon in Cianjur Regency - Alfan, Muhammad; Supriyadi, Yogi (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2025)
The Empty Horse tradition in Cianjur Regency of West Java of Indonesia holds an anthropological allure that symbolizes the courage, resilience, and aspirations of the local community in navigating historical social and political challenges. However, modernization has led to the diminishing recognition of its profound values, especially among younger generations. This study aims to explore the symbolism embedded in the Empty Horse tradition and its connection to the cultural identity of the Cianjur community, as well as strategies for its preservation through education and modern media. Employing a qualitative phenomenological approach, the research collected data through in-depth interviews, field observations, and literature reviews. Analysis was conducted using Lévi-Strauss' structuralism perspective to uncover the symbolic meanings and values inherent in this tradition. The findings reveal that the Empty Horse tradition is not only a symbol of diplomacy and wisdom in Cianjur’s history but also an essential tool for strengthening social cohesion and local identity. The study concludes by emphasizing the importance of concrete measures such as documentation, cultural education, and the promotion of this tradition at both local and global levels. This research contributes to a deeper understanding of local cultural heritage and highlights opportunities to integrate it into the global cultural framework.